Suddenly Home: Returned Women Migrant Workers due to COVID-19 Pandemic Seeking Emergency Income and Equal Gender Roles in the Household - Theresia Octastefani; Bayu Mitra A. Kusuma (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The COVID-19 pandemic stopped practically all activities in almost all sectors of the economy, resulting in an unprecedented global economic crisis. One of the impacts was that millions of women migrant workers lost their jobs in their host countries. This article explores the struggle of Indonesian women migrant workers as they returned to their hometowns in Banyuwangi Regency due to the COVID‐19 pandemic and were forced to find an alternative source of income for their families. This qualitative study uses literature studies and in-depth interviews to collect data and information. The results show that women took a heavier share of the workload in supporting their household during the pandemic. As a breadwinner, they had to quickly adapt to the situation and earn an income as soon as they returned home. They struggled to look for alternative sources of income in rural areas, which were limited to farming, online ride-hailing services (individual efforts), and SME activities (collective efforts), such as producing garments, food and fruit products, livestock, and crafts. For these women, the fear of being exposed to COVID-19 was pale in comparison to the fear of not being able to provide for the family. At the same time, once home, the workload from housework is theirs, doubling their burden.